Dampak Kepemimpinan dan Strategi Manajemen Perubahan pada Budaya Organisasi - Muhammad Indra Pratama; Nuri Aslami (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
In this paper, we present the impact of leadership and change management strategy on organizational culture. At first, we present the notion of culture. There are many attempts to describe “organizational culture”, many of which are presented in this paper. After an assessment of organizational culture, the role of leader is pinpointed. We favor the view that strategic leadership needs to be transformational if it is to serve the organization. Afterwards, the notion of change is focused on. Changing a culture is a large-scale undertaking and all of the organizational tools for changing minds will need to be put in play. To change or to manage corporate culture one has to be able to define and therefore pinpoint exactly what it is one is trying to change. The evidence in this study suggests that leadership is associated with organizational culture, primarily through the processes of articulating a vision and to a lesser extent through the setting of expectations. The nature of this paper is explorative and theoretical, aiming at providing a bibliographical tool for further research. Thus, aim of this paper is a critical bibliographical review of important terms in the field, as well as showing the interdependencies of these terms. Finally, with that paper, we offer managers and researchers a model on emphasizing the importance of Management Strategy